2014
DOI: 10.5530/fra.2014.2.3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro action of 2.2’-azobis-2 amidinopropan dihydrochloride,red wine polyphenols, resveratrol and catechin on anion permeability for chloride in human red blood cell

Abstract: Introduction:The purpose of this study was to evaluate the ability of polyphenols (red wine polyphenols, resveratrol and catechin) on anion permeability for chloride and oxidative damage in human erythrocytes exposed to the water-soluble free radical initiator 2.2'-azobis-2 amidinopropan dihydrochloride (AAPH). Materials and Methods: The reducing agent treatment efficacy was observed by evaluation of anion permeability for chloride, lipid peroxidation and hemolysis in red blood cells (RBCs). Anion permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…3 In a recent paper 5 authors demonstrated that hypertriglyceridemia affects Red Blood Cell membrane oxidative status (increase of [MDA] and [HNE] to membrane protein ratio) is increased by high levels of blood cholesterol, but selectively by hypertriglyceridemia. 5,6 It is known that Cr protects the erythrocytes by attenuating the AAPH and H 2 O 2 induced alterations. 6 This protective effect was confirmed by electron microscopic analysis which showed that oxidant-induced cell damage was attenuated by Cre.…”
Section: Introductionmentioning
confidence: 99%
“…3 In a recent paper 5 authors demonstrated that hypertriglyceridemia affects Red Blood Cell membrane oxidative status (increase of [MDA] and [HNE] to membrane protein ratio) is increased by high levels of blood cholesterol, but selectively by hypertriglyceridemia. 5,6 It is known that Cr protects the erythrocytes by attenuating the AAPH and H 2 O 2 induced alterations. 6 This protective effect was confirmed by electron microscopic analysis which showed that oxidant-induced cell damage was attenuated by Cre.…”
Section: Introductionmentioning
confidence: 99%
“…4-hydroxytyrosol shows a substantial degree of inhibition against ascorbate-Fe 2+ induced LPO in rat liver microsomes. [ 6 ] In a previous study of Gallo and Martino[ 7 ] on RBC membranes damages by oxidant agents, authors demonstrated the conformational alterations and polyphenols repairing in the same structure. Among the known risk factors of atherosclerosis-associated oxidative stress are hyperlipidemia and/or hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] 4-hydroxytyrosol is shown to significantly protect RBCs from oxidative damage (LPO [4-HNE]). The authors[ 7 ] studied the protective effect of 4-hydroxytyrosol on human RBCs and oxidative damage so, the intent is to examine the role of triglycerides overload on degradation of membrane lipids in the presence of other reducing agents (protective effect of 4-hydroxytyrosol). For instance, in complete eukaryotic cells, the following damages can happen: 4-HAE are endogenous ligands for peroxisome proliferator-activated receptor-δ.…”
Section: Introductionmentioning
confidence: 99%